2018
DOI: 10.1093/jamia/ocy131
|View full text |Cite
|
Sign up to set email alerts
|

Expert-level sleep scoring with deep neural networks

Abstract: ObjectivesScoring laboratory polysomnography (PSG) data remains a manual task of visually annotating 3 primary categories: sleep stages, sleep disordered breathing, and limb movements. Attempts to automate this process have been hampered by the complexity of PSG signals and physiological heterogeneity between patients. Deep neural networks, which have recently achieved expert-level performance for other complex medical tasks, are ideally suited to PSG scoring, given sufficient training data.MethodsWe used a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(178 citation statements)
references
References 37 publications
8
163
0
7
Order By: Relevance
“…In contrast to previous studies, the 2018 PhysioNet Challenge offered us a unique opportunity to truly evaluate the performances and compare cutting-edge methods on a large external hidden test set of 989 samples 23 . In addition, we demonstrate that deep convolutional neural networks trained on full-length records and multiple physiological channels have the best performance in detecting sleep arousals, which are quite different from current approaches extracting features from short 30-second epochs 25,27,30 . Beyond sleep arousals, we propose that the U-Net architecture used in DeepSleep can be adapted to other segmentation tasks such as sleep staging.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast to previous studies, the 2018 PhysioNet Challenge offered us a unique opportunity to truly evaluate the performances and compare cutting-edge methods on a large external hidden test set of 989 samples 23 . In addition, we demonstrate that deep convolutional neural networks trained on full-length records and multiple physiological channels have the best performance in detecting sleep arousals, which are quite different from current approaches extracting features from short 30-second epochs 25,27,30 . Beyond sleep arousals, we propose that the U-Net architecture used in DeepSleep can be adapted to other segmentation tasks such as sleep staging.…”
Section: Discussionmentioning
confidence: 57%
“…S2G-H ). It has also been reported that neural network approaches significantly outperformed classical machine learning methods, including random forest, logistic regression 25 , support vector machine, and linear models 26 . In fact, 8 out of the top 10 teams used neural network models in the 2018 PhysioNet Challenge (red blocks in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning approaches can be used to accurately estimate sleep states. We previously showed that deep neural networks can learn to score conventional sleep stages based on EEG signals obtained during overnight PSG with an accuracy of 87.5% and a Cohen's kappa of 0.805, comparable to the performance of human sleep scoring experts 17 . Here we develop deep neural networks using ECG and/or respiratory signals to classify sleep stages.…”
Section: Introductionmentioning
confidence: 85%
“…Uses of convolutional and recurrent neural networks have been shown to achieve state-of-the-art performance in various fields [17,32], including sleep analysis [3,33,34]. A convolutional neural network (CNN) works by taking a static input such as a signal or image, and the CNN processes it with a network of filters.…”
Section: Classification With Convolutional and Lstm Neural Networkmentioning
confidence: 99%